Research on Key Control Technology of Intelligent Rolling Contact Fatigue Test Facility - Jianyao Li; Juke Liang; Gubo Chen; Yan Yang (Journal of Control Science and Engineering)
An intelligent rolling contact fatigue test equipment is developed, and the control methods are presented. For obtaining the slip accurately, the control method based on master-slave synchronization is proposed. For controlling the loads in high precision, the control method took into consideration the influence by two factors, displacement and the load. The nonlinear interference and excess torque in load control are effectively suppressed. Based on the SIMOTION D425 which is the Siemens integrated motion control system, the control system architecture of the intelligent rolling contact fatigue test equipment is constructed. The solutions of slip ratio and the experimental load controlled by these methods are satisfactory with the requirement of design precision. In the validation experiment, the load control accuracy is ±3%, the average error of load control is 1.77%, and the average error of slip control is 0.26%. The experiment results show the proposed control methods are feasible and effective.